The Impact of Knowledge Sharing and Work Motivation on Employee Performance PT Altrak 1978 Sampit Branch, Central Kalimantan - Rejeki Amalia Yubairi; Dian Indiyati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this study was to find out the influence of Knowledge Sharing on Employee Performance, the influence of Work Motivation on Employee Performance, then the influence of both Knowledge Sharing and Work Motivation on Employee Performance, at PT Altrak 1978 Sampit Branch, Central Kalimantan. This study uses quantitative methods with questionnaire data collection techniques distributed to all employees because the sampling technique used is a saturated sample, so all 142 population members will be sampled. Based on the data analysis technique used is path analysis with the help of IBM SPSS software version 25. There is a simultaneous and partial significant influence of each variable, both knowledge sharing and work motivation, on employee performance, with a total influence of knowledge sharing of 53.8%. Meanwhile, the total effect of work motivation is 26.9%.